Prosocial development a multidimensional approach - Padilla-Walker, Laura M.; Carlo, Gustavo (Oxford University Press, 2014)
Prosocial behaviour - broadly defined as voluntary action intended to help or benefit another - has been associated with positive outcomes across the lifespan. Children with a more prosocial orientation are better liked and trusted by their peers, have a higher status in peer groups, are better at maintaining friendships, demonstrate better self regulation, empathy, and social cognitive skills, and excel in academics. This text examines a variety of biological, socialization, and contextual influences on prosocial development from infancy through early adulthood.